Effect of hBN Nanoparticle-Enhanced Engine Oil on the Tribological Behaviour of Al7075 Alloy - Macit, Cevher Kursat; Horlu, Merve; Tanyeri, Burak; Aksakal, Bunyamin (Wiley, 2026)
Aluminium alloys, particularly Al7075, are extensively employed in aerospace and automotive applications owing to their high strength-to-weight ratio; however, their limited wear resistance under severe sliding conditions restricts wider utilisation. In this study, the tribological behaviour of Al7075 was systematically investigated under dry sliding, base oil lubrication, and lubrication with SAE 5 W-30 engine oil reinforced with hexagonal boron nitride (hBN) nanoparticles. The lubricant was modified with 1, 5, and 10 wt.% hBN, and the corresponding rheological behaviour was characterised prior to tribological testing. Pin-on-disc experiments were conducted under normal loads ranging from 10 to 50 N. In parallel, a tactile sensor-based approach was employed to reconstruct three-dimensional wear topographies, enabling quantitative assessment of wear depth and surface morphology. The results demonstrate that hBN nanoparticle reinforcement significantly enhances frictional and wear performance. The addition of hBN increased lubricant viscosity by approximately 25%, thereby improving load-bearing capacity and interfacial film stability. Under the highest applied load (50 N), dry sliding resulted in severe material loss (622 mg), whereas lubrication with 10 wt.% hBN reduced wear loss to 44 mg. The coefficient of friction decreased monotonically with increasing hBN concentration, reaching an overall reduction of approximately 90% relative to dry sliding conditions. SEM/EDS and cross-sectional analyses confirmed the formation of continuous hBN-rich tribo-layers with thicknesses in the range of similar to 200-500 nm. These tribo-layers acted as low-shear solid-lubricating films that filled surface grooves, reduced crack initiation, and promoted self-replenishing behaviour through debris compaction. Combined cross-sectional, topographical and tactile sensor analyses revealed a clear transition in dominant wear mechanisms. While unreinforced Al7075 exhibited severe abrasive, adhesive, and delamination wear, hBN-reinforced lubrication transformed the wear response toward milder abrasion coupled with controlled oxidative wear. The strong agreement between gravimetric wear measurements and sensor-based reconstructions further validated the reliability of the tactile sensing methodology for high-resolution wear characterisation. Overall, the integration of hBN-enhanced lubrication with tactile sensor-based wear quantification provides a robust and cost-effective strategy to reduce friction, suppress severe wear, and extend the service life of Al7075 components operating under high-load and boundary lubrication conditions.
Keywords: 3D surface topography; aluminium 7075; hexagonal boron nitride; self-lubricating; tactile tactical sensor; tribology